The Innovation Procurement Policies and the Development of e‑health in the EU Member States: What Can Be Learnt? - Kautsch, Marcin; Lichoń, Mateusz; Matuszak, Natalia (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article presents findings of research on e‑health development in four European Union (EU) Member States in the context of public procurement of innovation (PPI). EU policies attempt to make public procurement leverage for innovation by introducing a number of new tender procedures. Policies and practices in PPI, including e‑health, were investigated for Denmark, Great Britain, Spain and Poland. For various reasons, all four countries struggle with the introduction of the European PPI procedures, and with making a transition to outcome‑based tenders. Though they all introduced policies implementing these procedures, Denmark and Great Britain seem to have achieved better results, having well‑established public‑private collaboration. This correlates with a more efficient adoption of e‑health solutions in those countries. With some minor successes, Spain, and particularly Poland, display attachment to traditional procedures despite changes in the public procurement regulations.